Early versus delayed surgery for paediatric supracondylar humeral fractures in the absence of vascular compromise: a systematic review and meta-analysis. (December 2018) - Farrow, L.; Ablett, A. D.; Mills, L.; Barker, S.
Abstract : Aims: We set out to determine if there is a difference in perioperative outcomes between early and delayed surgery in paediatric supracondylar humeral fractures in the absence of vascular compromise through a systematic review and meta-analysis. Materials and Methods: A literature search was performed, with search outputs screened for studies meeting the inclusion criteria. The groups of early surgery (ES) and delayed surgery (DS) were classified by study authors. The primary outcome measure was open reduction requirement. Meta-analysis was performed in the presence of sufficient study homogeneity. Individual study risk of bias was assessed using the Risk of Bias in Non-Randomised Studies – of Interventions (ROBINS-I) criteria, with the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) criteria used to evaluate outcomes independently. Results: A total of 12 studies met the inclusion criteria (1735 fractures). Pooled mean time to surgery from injury was and 10.7 hours for ES and 91.8 hours for DS. On meta-analysis there was no significant difference between ES versus DS for the outcome of open reduction requirement. There was also no significant difference for the outcomes: Iatrogenic nerve injury, pin site infection, and re-operation. The quality of evidence for all the individual outcomes was low or very low. Conclusions: There is no evidence that delaying supracondylar fracture surgery negatively influences outcomes in the absence of vascular compromise. There are, however, notable limitations to the existing available literature.